Peran dan Kedudukan Perempuan dalam Novel Hati Suhita Karya Khilma Anis - Lestari, Evi Dwi (CV. Eduartpia Publisher, 2023)
In the novel Hati Suhita there are gender problems in the form of stereotypes, subordination, and marginalization. However, it does not have an impact on differentiating the roles and positions of women and men. Women can do everything men do. Women can be leaders, teach, be active in writing (journalism), and others. The values of character education in the novel Hati Suhita by Khilma Anis include istiqomah, tawadhu 'sincere, obedient wife, hard worker, trustworthy, patient and tenacious.The conclusion of this research is that Hati Suhita Novel is a novel that tells about a woman who strongly adheres to the Javanese philosophy of Mikul Duwur Mendem Jeru. In the novel Hati Suhita not only critically describes the personality of a woman, but also knowledge about the position of women in the structure of society, which is represented in society as weak beings, lacks intelligence, and tends to be passive. In the novel, women are not only presented as intelligent figures, but also as people who have strong personalities and have the courage to actualize themselves in society. However, this does not mean that in the novel Hati Suhita there are no gender problems. However, the gender problems that occur in the novel Hati Suhita are balanced by the strong attitude of a woman implied in the novel.Keywords: Role and Position of Women, Feminism and the Novel Hati Suhita by Khilma Anis.